Stochastically-driven multidecadal variability of the Atlantic meridional overturning circulation in CCSM3 - Kwon, Young-Oh; Frankignoul, Claude (Climate Dynamics, 2012)
International audience The Atlantic meridional overturning circulation (AMOC) in the last 250 years of the 700-year-long present-day control integration of the Community Climate System Model version 3 with T85 atmospheric resolution exhibits a red noise-like irregular multi-decadal variability with a persistence longer than 10 years, which markedly contrasts with the preceding ~300 years of very regular and stronger AMOC variability with ~20 year periodicity. The red noise-like multi-decadal AMOC variability is primarily forced by the surface fluxes associated with stochastic changes in the North Atlantic Oscillation (NAO) that intensify and shift northward the deep convection in the Labrador Sea. However, the persistence of the AMOC and the associated oceanic anomalies that are directly forced by the NAO forcing does not exceed about 5 years. The additional persistence originates from anomalous horizontal advection and vertical mixing, which generate density anomalies on the continental shelf along the eastern boundary of the subpolar gyre. These anomalies are subsequently advected by the mean boundary current into the northern part of the Labrador Sea convection region, reinforcing the density changes directly forced by the NAO. As no evidence was found of a clear two-way coupling with the atmosphere, the multi-decadal AMOC variability in the last 250 years of the integration is an ocean-only response to stochastic NAO forcing with a delayed positive feedback caused by the changes in the horizontal ocean circulation.